Hibbs, Doreen (London, 2013)
2013 "Hibbs, Doreen", 2013, HistoryTalk Doreen was born in Raddington Road off Portobello Road. She worked at the tinning factory on Latimer Road, at a bakers and deli on Portobello Road, a bakers in Shepherds Bush, and as a school cleaner for 15 years. Doreen is married to Fred and they have had five children.